The new encyclopedia británica in 30 volumes, macropedia VOL. 15 / William Benton - Benton, William (1977)
General features, natural history, evolution and classification, family gomphotheridae, roman law, medieval Europe, period of national codifications in Europe, considerations prior to trial or main hearing, the trial and the main hearing, appeals and other methods of review, general features, natural history, form and function, evolution and classification, costs the short run, output in the short run.